Integrating Software Testing to CS Curriculum Using WRESTT-CyLE - Fu, Yujian; Clarke, Peter J; Barnes, Nelson (Association for Engineering Education - Engineering Library Division Papers, 2016)
WRESTT-CyLE is a cyber enabled virtual learning environment that provides students and educators with fruitful information of software testing, supports various type of teaching materials in the form Learning Objects, and facilitates with social and media networking and peer study environments. Virtual Learning Environment has become a major field of interest in recent years, with the integration of multiple social and media networking applications, it has been dominated in current academic learning environment and peer learning support. In this paper, we presented the computer science course study of multiple subjects by using WRESTT-CyLE to teach software testing concepts. Software testing is a high level concept and not widely offered in many computer science programs. Due to the conceptual complexity and large amount of fundamental knowledge of software engineering and system development, teaching software testing with the identified required courses is very challenge. It is still very hard for students to have a well understanding of concepts. WRESTT-CyLE, a cyber enabled virtual learning environment of software testing for students to improve learning by integrate it to the internet technology. This study performed at Alabama A&M University aims at three objectives. First, foster students’ acquisition of software testing concepts and skills in upper level undergraduate courses with a programming component. Second, disseminate the research findings in use of WRESTT-CyLE and success stories from the project. Third, access to a cyber learning environment that supports different student learning strategies.